Phenotypic and Genotypic Features of Thai Patients With Nonsyndromic Tooth Agenesis and WNT10A Variants - Kanchanasevee, Charinya; Sriwattanapong, Kanokwan; Theerapanon, Thanakorn; Thaweesapphithak, Sermporn; Chetruengchai, Wanna; Porntaveetus, Thantrira; Shotelersuk, Vorasuk (Frontiers in Physiology, 2020)
Tooth agenesis is one of the most common orodental anomalies that demonstrate phenotypic and genotypic heterogeneity with a prevalence of 2.5%–7%. Mutations in WNT10A have been proposed to be the most common cause of nonsyndromic tooth agenesis (NSTA). The aim of this study was to characterize the dental features and genetic variants of NSTA in a Thai population. We recruited 13 unrelated patients with NSTA who attended the Faculty of Dentistry, Chulalongkorn University, Thailand, from 2017 to 2019. All 13 underwent whole exome sequencing that identified likely pathogenic genetic variants, all in WNT10A, in five patients. All five patients had second premolar agenesis, while three also had absent or peg-shaped upper lateral incisors. Patient 1 possessed a novel heterozygous duplication, c.916_918dupAAC (p.Asn306dup) in WNT10A. Patients 2 and 3 harbored a heterozygous and homozygous c.637G > A (p.Gly213Ser) in WNT10A, respectively. Patients 4 possessed a heterozygous c.511C > T (p.Arg171Cys) in WNT10A. Patient 5 harbored a homozygous c.511C > T (p.Arg171Cys) in WNT10A and a novel heterozygous c.413A > T (p.Asn138Ile) in EDARADD, suggesting digenic inheritance. We recruited another 18 family members of these five patients. Out of 23 participants, homozygous WNT10A variants were identified in 2 patients and heterozygous variants in 17 individuals. Both homozygous patients had NSTA. Eight out of 17 heterozygous individuals (8/17) had NSTA or a peg-shaped lateral incisor, indicating a 47% penetrance of the heterozygous variants or 53% (10/19) penetrance of either homozygous or heterozygous variants in WNT10A. The frequencies of the c.511C > T in our in-house 1,876 Thai exome database, Asian populations, and non-Asian populations were 0.016, 0.005–0.033, and 0.001, respectively; while those of the c.637G > A were 0.016, 0.004–0.029, and 0.000, respectively. In conclusion, our study reports two novel variants with one each in WNT10A and EDARADD, expanding the genotypic spectra of NSTA. Second premolar agenesis is a common phenotype in affected individuals with variants in WNT10A; however, its penetrance is incomplete. Lastly, the different frequencies of WNT10A variants, c.511C > T and c.637G > A, in diverse populations might contribute to the prevalence range of NSTA between continents.